2017
DOI: 10.1177/2333721417713422
|View full text |Cite
|
Sign up to set email alerts
|

End of Life Care and Do Not Resuscitate Orders: How Much Does Age Influence Decision Making? A Systematic Review and Meta-Analysis

Abstract: With population aging, “do not resuscitate” (DNAR) decisions, pertaining to the appropriateness of attempting resuscitation following a cardiac arrest, are becoming commoner. It is unclear from the literature whether using age to make these decisions represents “ageism.” We undertook a systematic review of the literature using CINAHL, Medline, and the Cochrane database to investigate the relationship between age and DNAR. All 10 studies fulfilling our inclusion criteria found that “do not attempt resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 51 publications
4
31
0
1
Order By: Relevance
“…2,3 It has been found that age increases the use of "do not resuscitate" orders, but it is unclear from the literature whether using age to make these decisions represents "ageism". 21 One of the important points that emerge from our results is that patients with dementia living in nursing homes came in ED to die. One hypothesis is that there are few advance directives as found in a previous study 14 and no anticipation about end-of-life decision before admission in ED.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2,3 It has been found that age increases the use of "do not resuscitate" orders, but it is unclear from the literature whether using age to make these decisions represents "ageism". 21 One of the important points that emerge from our results is that patients with dementia living in nursing homes came in ED to die. One hypothesis is that there are few advance directives as found in a previous study 14 and no anticipation about end-of-life decision before admission in ED.…”
Section: Discussionmentioning
confidence: 82%
“…Concerning reasons for making decisions of withholding or withdrawing life‐sustaining treatments, we found that previous functional limitation and age were the most frequent criteria to justify limiting life‐support therapies, whereas previous studies found that acute medical disorder was the principal criteria . It has been found that age increases the use of “do not resuscitate” orders, but it is unclear from the literature whether using age to make these decisions represents “ageism” …”
Section: Discussionmentioning
confidence: 99%
“…[14] Tier 1 includes peoples' preferences for end-of-life care; choosing a place of death helps people to die at home, whereas people whose preference is unknown are more likely to be admitted to hospital for end-of-life care. [15] Lower proportions of the Asian participants in this study compared with westerners had expressed a preferred place of death or signed Do Not Resuscitate agreements, [16] which highlights an unmet need for advocacy to better prepare elderly Taiwanese people for death. The prevalence of frailty was similar to other reports.…”
Section: Discussionmentioning
confidence: 83%
“…an agreement between a patient and a health care professional not to attempt cardiopulmonary resuscitation in case of cardiac arrest. Since a DNR status is more often agreed upon by patients with higher age, 28 we assumed higher probabilities for higher aged patients. We assumed that for patients who suffered cardiac arrest with a DNR status, no CPR would be attempted and death is certain.…”
Section: Decision Treementioning
confidence: 99%